EFEKTIVITAS MODEL PEMBELAJARAN SURVEY QUESTION READ REFLECT RECITE REVIEW (SQ4R) UNTUK MENINGKATKAN KEMAMPUAN LITERASI MATEMATIKA PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL - Zakkiyatun Nisaa Fadhilatullathifi; Fadhilah Rahmawati; Aprilia Nurul Chasanah (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
This study aims to see the difference in the average mathematical literacy skills using the Survey Question Read Reflect Recite Review (SQ4R) model with the direct learning model and to see how effective the Survey Question Read Reflect Recite Review (SQ4R) model is to improve mathematical literacy skills in two-variable linear security system materials. This research approach is quantitatively through the design of quasi experimental pretest posttest. The population is all students of class VIII MTs N 1 Magelang City, while the sample is selected through random sampling and selects classes VIII A and VIII C as samples. Research data were collected through mathematical literacy proficiency tests in the form of pretests and posttests. Furthermore, the data were analyzed through SPSS with an Independent sample t test and an N-Gain test. The results showed that the results showed that 1) there was an average difference between the direct learning model and the SQ4R learning model; and 2) the SQ4R model is more effective for improving mathematical literacy skills